PELATIHAN DAN PENDAMPINGAN PEMBUATAN PERUSAHAAN STARTUP BAGI UMKM DEMI MENINGKATKAN KETAHANAN EKONOMI DI MASA PANDEMI COVID 19 - Fitri, Rahimi; Nugroho, Agus Setiyo Budi; Asyikin, Arifin Noor; Herlinawati, Herlinawati (Jurnal IMPACT: Implementation and Action, 2021)
The Covid-19 outbreak has had a negative impact on all sectors in the world, including Indonesia. The MSME business and also startups are among those affected. Significant impacts, such as decreased sales, reduction of employees, and losses to cover operating costs. Micro, small and medium enterprises (MSMEs) are the sectors most vulnerable to the impact of the Covid 19 pandemic. Currently, the MSME sector is considered to be no longer able to become one of the pillars of the Indonesian economy, such as during the 1998 and 2008 economic and financial crises. mats, and large companies that have to downsize the number of employees so that there are massive layoffs, the worst impact that occurs is an increase in divorce rates due to reduced income in households. This must be an important concern for the community to creatively create new business opportunities amid the COVID19 pandemic. Changes in people's buying behavior from buying directly to traders to buying online can be an opportunity to make changes in the economic sector. E-commerce companies in Indonesia recorded an increase in sales volume with more and more people implementing physical distancing in the midst of the Covid-19 outbreak. The government has also started to look at the e-commerce sector as a solution to overcoming the tax deficit due to the economic slowdown. Digital commerce has a very good opportunity in the midst of a pandemic which demands that people carry out social distancing, and opens opportunities for anyone to open new businesses after the pandemic. A digital startup company is a business that has just been established and is growing supported by digital services and still needs a lot of funding to operate with a minimalist work group. In Indonesia, there are currently many young entrepreneurs emerging to create startup businesses that have unlimited innovation and creativity. Based on the previous description, in community service activities with the community empowerment program scheme, it is intended to hold training and mentoring activities for MSMEs or people who already have business products to be able to build startup companies.